Computerised cognitive training tools and online nutritional group counselling for people with mild cognitive impairment: study protocol of a completely digital, randomised, controlled trial. Issue 7 (1st July 2022) - Scheerbaum, Petra; Book, Stephanie; Jank, Michael; Hanslian, Etienne; DellO'ro, Melanie; Schneider, Julia; Scheuermann, Julia-Sophia; Bösl, Sophia; Jeitler, Michael; Kessler, Christian; Graessel, Elmar
Abstract : Introduction: People with mild cognitive impairment (MCI) are at increased risk of decreasing cognitive functioning. Computerised cognitive training (CCT) and nutrition have been shown to improve the cognitive capacities of people with MCI. For each variable, we developed two kinds of interventions specialised for people with MCI (CCT: 'individualised' CCT; nutrition: a whole-food, plant-based diet). Additionally, there are two kinds of active control measures (CCT: 'basic' CCT; nutrition: a healthy diet following the current guidelines of the German Nutrition Society). The aim of this study is to investigate the effects of the two interventions on cognition in people with MCI in a 2×2 randomised controlled trial with German participants. Methods and analysis: Participants will be community-dwelling individuals with a psychometric diagnosis of MCI based on the Montreal Cognitive Assessment (MoCA) and Mini-Mental State Examination. With N=200, effects with an effect size of f ≥0.24 (comparable to Cohen's d ≥0.48) can be detected. Screening, baseline, t6 and t12 testing will be conducted via a videoconferencing assessment, telephone, and online survey. Participants will be randomly allocated to one of four groups and will receive a combination of CCT and online nutritional counselling. The CCT can be carried out independently at home on a computer, laptop, or tablet. Nutrition counselling includes 12 online group sessions every fortnight for 1.5 hours. The treatment phase is 6 months with follow-ups after six and 12 months after baseline. Ethics and dissemination: All procedures were approved by the Friedrich-Alexander-Universität Erlangen-Nürnberg Ethics Committee (Ref. 21-318-1-B). Written informed consent will be obtained from all participants. Results will be published in peer-reviewed scientific journals, conference presentations. Trial registration number: ISRCTN10560738 .